Maternal vaccination against respiratory syncytial virus infection in infants younger than 6 months: an integrative review - Marino, Patricia Mendes de Souza (Bionorte, 2025)
Objective: to synthesize the available scientific evidence on the efficacy of maternal vaccination against RSV infection in infants younger than 6 months. Methods: this study is an integrative literature review, designed according to the methodological framework proposed by Whittemore and Knafl12 and following the PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), ensuring rigor and transparency in the identification, selection, and synthesis of scientific evidence. The literature search was conducted in the electronic databases Scientific Electronic Library Online (SciELO), LILACS Plus Collection and BVS Complete Collection (via the Biblioteca Virtual em Saúde [BVS]). Search strategies were developed in both Portuguese and English using controlled descriptors (Descritores em Ciências da Saúde [DeCS] / MeSH terms) and combined through the Boolean operators AND and OR. Results: nine scientific articles on maternal RSV vaccination and its effects in infants under 6 months were analysed. The investigation consisted of multicentre observational studies in referral hospitals (Argentina and the United Kingdom) estimating effectiveness against RSV related hospitalization in infants <6 months, phase 3 clinical trials, randomized, double-blind, placebo-controlled trials of the RSVpreF vaccine (Pfizer, MATISSE), a phase 2 and a phase 3 study of RSVPreF3-Mat (GSK), a phase 3 Novavax trial with a nanoparticle antigen and age-structured epidemiological modelling projecting population impact. Conclusion: maternal vaccination was effective in reducing hospitalizations and severe RSV associated lower respiratory tract infection in newborns and infants up to 6 months of age, with a favorable safety profile. The RSVpreF vaccine (Pfizer) demonstrated a favorable safety profile with no signals of concern. However, the RSVPreF3-Mat vaccine (GSK) showed a signal of increased preterm birth (6.8% vs 4.9%, p=0.01), leading to early trial termination. Ongoing safety surveillance and post-implementation studies are warranted to refine the magnitude of benefit and to characterize potential risks across diverse populations and settings.